Self‐completed online dietary recalls as an alternative method of dietary assessment for dietetic outpatient appointments: A feasibility study. Issue 1 (14th July 2022) - Gianfrancesco, Carla; Taylor, Carolyn; Croot, Liz
Abstract: Background: Integrating digital dietary assessment within dietetic care could save time and reduce costs, at the same time as increasing patient engagement. The present study explores the feasibility of implementing a web‐based dietary assessment tool, myfood24 (https://www.myfood24.org ), into routine healthcare. Methods: This mixed methods feasibility study recruited dietitians and patients from a National Health Service (NHS) hospital outpatient setting. Patients completed and shared three online 24‐h dietary recalls in advance, which were used as a dietary assessment by dietitians. Recruitment data were collected and questionnaires on technology, usability, and acceptability were completed. Patient interviews and focus groups with dietitians were conducted. Results: Eleven dietitians working in allergy, bariatrics, diabetes, oncology, general, renal, infectious diseases, and coeliac services took part with 39 patients. Recruitment rates were highest in bariatrics and lowest in renal and oncology. Compared to other studies, completion rates were good, with 29 (74.4%) completing three recalls despite lower technology readiness and software usability scores than in similar studies. Illness and difficulty with technology were reasons for non‐completion. Opportunity to receive nutritional feedback from the tool and share this with a dietitian motivated patients to complete the record accurately. Consultation times were shortened in approximately one‐third of appointments and a higher proportion of time was spent on nutritional education compared to usual practice. However, mean preparation time increased by 13 min per appointment because dietitians found nutritional analysis reports difficult to interpret. Conclusions: It is feasible to introduce a digital dietary assessment tool into NHS dietetic practice. However, further development is needed to ensure that the tool is suitable for healthcare. Abstract : Evaluation of self‐completed online dietary recalls in clinical dietetic practice. Key points: This is likely to be the first study in the UK investigating the use of digital dietary assessment in clinical dietetic practice. Seven different clinical specialities were included. Recruitment rates were highest in bariatrics and lowest in oncology and renal where ill health was given as a main reason for non‐participation. Non‐completers had low technology readiness scores, which may suggest this tool could be used to identify individuals who may need more technological support. Dietitians reported that clinic preparation time took longer than usual care, but time was saved in one‐third of consultations and more time was available for patient education. The intervention was moderately acceptable to patients and dietitians, although tailoring the software to clinical care and the availability of an app would likely improve this further.